The Legal Nature of Electric Transmission Planning in Peru - Díaz Villanueva , Edwar Rafael (Revista de Derecho, 2025)
The transmission plan includes binding projects approved by the Ministry of Energy and Mines, which must be implemented over a 10-year period to ensure the quality, safety and efficiency of the national electricity system. This planning is carried out within the framework of the state duty to ensure the efficiency and continuity of the electricity supply. This document evaluates the criteria of generality, innovation and consumption to determine whether the transmission plan is a normative or administrative act. The general character of the plan is reviewed in accordance with these criteria, which does not necessarily determine whether it is a rule or an administrative act, since there are acts that have a general character and rules with particular application. The plan is also derived from a law, but requires other acts to be implemented. Finally, the plan is ended by fulfilling its purpose, which is the execution of binding projects, a situation that brings it closer to being an administrative act; in addition to being approved following an administrative procedure and falling within the definition of an administrative act. We concluded that, despite certain particularities, the transmission plan fits within the concept of administrative act as far as binding projects are concerned, and can therefore be challenged through administrative appeals and reviewed judicially. It also applies the concept of revocation in cases referred to when the conditions required for its issuance occur or elements that favor the addressee of the act and do not harm third parties.